Oral absorption enhancement of salmon calcitonin by using both N-trimethyl chitosan chloride and oligoarginines-modified liposomes as the carriers. (August 2014) - Huang, Aiwen; Su, Zhigui; Li, Sai; Sun, Minjie; Xiao, Yanyu; Ping, Qineng; Deng, Yanping
Abstract In this study both N-trimethyl chitosan chloride (TMC) and oligoarginine (Arg8) were utilized to modify liposomes as the multifunctional carriers (TMC-Arg8-Lips) for enhancing the oral absorption of salmon calcitonin. Two permeation enhancers with positive charges were sequentially adsorbed on the liposomal surface with negative charges by electrostatic interaction. Instead of salmon calcitonin, fluorescein isothiocyanate dextran (FD4) was loaded in TMC-Arg8-Lips for Caco-2 cell permeation test in vitro and penetration examination in rat intestinal tract in vivo. The results showed that the apparent permeability coefficient (Papp) of TMC-Arg8-Lips containing FD4 were 7.0-, 4.4-, 1.8- and 1.4-folds higher than FD4 solution, FD4-TMC solution, non-modified liposomes (Non-Lips) and TMC modified liposomes (TMC-Lips), respectively. A strong fluorescence was observed by confocal laser scanning microscope (CLSM) at rat intestinal wall isolated in different times after the FD4 loaded carriers were intragastrically administrated. Furthermore, the images revealed that TMC-Arg8-Lips could penetrate deeply inside the mucosal membrane. The pharmacodynamic study indicated that TMC-Arg8-Lips containing calcitonin were more efficient in enhancing the absorption and prolonging the reduction of blood calcemia in rats. The area above the plasma calcium concentration–time curve (AAC) of TMC-Arg8-Lips containing calcitonin was increased by more than 16.6- and 1.6-fold when compared to Non-Lips and TMC-Lips, respectively.